Topical anti-inflammatory effect of hydroalcoholic extract of leaves of Licania rigida Benth. in mice - Enaide Soares Santos; Cícera Datiane de Morais Oliveira-Tintino; Denise Bezerra Correia; Cícero Damon Carvalho de Alencar; Maria de Fátima Sousa; Cícera Norma Fernandes Lima; Sara Tavares de Sousa Machado; Acléssia Damiana Soares Gomes; Francisca Adilfa de Oliveira Garcia; Irwin Rose Alencar Menezes; Aline Augusti Boligon; José Galberto Martins da Costa; et al. (Phytomedicine Plus, 2021)
Background: The use of medicinal plants is one of the oldest practices of humanity, its use is aimed at the treatment, cure and prevention of diseases. The plant Licania rigida Benth., popularly known as icticic, is used in folk medicine to treat flu, diarrhea, epilepsy and malaria, having some scientifically proven biological activities, such as its antioxidant, antimicrobial, bactericidal and systemic anti-inflammatory action. Methods: Thus, the present study aims to evaluate the topical anti-inflammatory activity of the hydroalcoholic extract obtained from the L. rigida leaves. Results: A possible topical anti-inflammatory action was observed in screening models such as acute and chronic ear edema. In addition, in the protocols for acute inflammation, the extract had an anti-hematogenic potential. Conclusions: The results are promising and can be a useful tool for more specific and effective studies on the anti-inflammatory effect in the construction of future drugs for improvement in cases of inflammation.